Viral infections of the central nervous system in Spain: A prospective study. Issue 3 (12th December 2012) - de Ory, F.; Avellón, A.; Echevarría, J.E.; Sánchez‐Seco, M.P.; Trallero, G.; Cabrerizo, M.; Casas, I.; Pozo, F.; Fedele, G.; Vicente, D.; Pena, M.J.; Moreno, A.; et al.
Abstract The aim of the study was to determine the incidence of viruses causing aseptic meningitis, meningoencephalitis, and encephalitis in Spain. This was a prospective study, in collaboration with 17 Spanish hospitals, including 581 cases (CSF from all and sera from 280): meningitis (340), meningoencephalitis (91), encephalitis (76), febrile syndrome (7), other neurological disorders (32), and 35 cases without clinical information. CSF were assayed by PCR for enterovirus (EV), herpesvirus (herpes simplex [HSV], varicella‐zoster [VZV], cytomegalovirus [CMV], Epstein–Barr [EBV], and human herpes virus‐6 [HHV‐6]), mumps (MV), Toscana virus (TOSV), adenovirus (HAdV), lymphocytic choriomeningitis virus (LCMV), West Nile virus (WNV), and rabies. Serology was undertaken when methodology was available. Amongst meningitis cases, 57.1% were characterized; EV was the most frequent (76.8%), followed by VZV (10.3%) and HSV (3.1%; HSV‐1: 1.6%; HSV‐2: 1.0%, HSV non‐typed: 0.5%). Cases due to CMV, EBV, HHV‐6, MV, TOSV, HAdV, and LCMV were also detected. For meningoencephalitis, 40.7% of cases were diagnosed, HSV‐1 (43.2%) and VZV (27.0%) being the most frequent agents, while cases associated with HSV‐2, EV, CMV, MV, and LCMV were also detected. For encephalitis, 27.6% of cases were caused by HSV‐1 (71.4%), VZV (19.1%), or EV (9.5%). Other positive neurological syndromes included cerebellitis (EV and HAdV), seizures (HSV), demyelinating disease (HSV‐1 and HHV‐6), myelopathy (VZV), and polyradiculoneuritis (HSV). No rabies or WNV cases were identified. EVs are the most frequent cause of meningitis, as is HSV for meningoencephalitis and encephalitis. A significant number of cases (42.9% meningitis, 59.3% meningoencephalitis, 72.4% encephalitis) still have no etiological diagnosis. J. Med. Virol. 85:554–562, 2013. © 2012 Wiley Periodicals, Inc.